5(x-1)+1=3x+2(-1+x)

Simple and best practice solution for 5(x-1)+1=3x+2(-1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-1)+1=3x+2(-1+x) equation:



5(x-1)+1=3x+2(-1+x)
We move all terms to the left:
5(x-1)+1-(3x+2(-1+x))=0
We add all the numbers together, and all the variables
5(x-1)-(3x+2(x-1))+1=0
We multiply parentheses
5x-(3x+2(x-1))-5+1=0
We calculate terms in parentheses: -(3x+2(x-1)), so:
3x+2(x-1)
We multiply parentheses
3x+2x-2
We add all the numbers together, and all the variables
5x-2
Back to the equation:
-(5x-2)
We add all the numbers together, and all the variables
5x-(5x-2)-4=0
We get rid of parentheses
5x-5x+2-4=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation

See similar equations:

| 40+14y=-20-8y-7 | | 10c=-5(-2c+3) | | 9=3k-6 | | -4+1x=-6+1/5x | | 17+x=127 | | 3(x+6)/6+34=41 | | 2=x÷4-2 | | 39/2=78/x | | 39+27+f=180 | | 6–11x=7x–12 | | 6(x=2)=180 | | 5x+35x-10=8(5x+7) | | 7u+2=-13 | | -18p-8=4(-7p+18) | | 88+100x=27x+75x-86 | | 1290=h/10+h/15 | | -4+1x=-6+(1/5)x | | 5x+10(120-x)=1050 | | 1/2x-9=1/4+3 | | 115+31+e=180 | | u7+2=-13 | | 9/3=36/n | | 2x-1+46=165 | | (7n-2)(5n-6)=0 | | 3n−2=1 | | (1)/(5)a=5 | | -5(x+4)=-50 | | -6+x/2=8 | | 0=13-4(8-5n | | 5x+4,7x−2,8x−5=180 | | 9x+2=190 | | -4+5x=x-11+5x |

Equations solver categories